Polymer particles for the intra-articular delivery of drugs to treat osteoarthritis. (2nd April 2021) - Mei, Xueli; Villamagna, Ian J; Nguyen, Tony; Beier, Frank; Appleton, C Thomas; Gillies, Elizabeth R
Abstract: Osteoarthritis (OA) is a leading cause of chronic disability. It is a progressive disease, involving pathological changes to the entire joint, resulting in joint pain, stiffness, swelling, and loss of mobility. There is currently no disease-modifying pharmaceutical treatment for OA, and the treatments that do exist suffer from significant side effects. An increasing understanding of the molecular pathways involved in OA is leading to many potential drug targets. However, both current and new therapies can benefit from a targeted approach that delivers drugs selectively to joints at therapeutic concentrations, while limiting systemic exposure to the drugs. Delivery systems including hydrogels, liposomes, and various types of particles have been explored for intra-articular drug delivery. This review will describe progress over the past several years in the development of polymer-based particles for OA treatment, as well as their in vitro, in vivo, and clinical evaluation. Systems based on biopolymers such as polysaccharides and polypeptides, as well as synthetic polyesters, poly(ester amide)s, thermoresponsive polymers, poly(vinyl alcohol), amphiphilic polymers, and dendrimers will be described. We will discuss the role of particle size, biodegradability, and mechanical properties in the behavior of the particles in the joint, and the challenges to be addressed in future research.